2018
DOI: 10.1002/smll.201804271
|View full text |Cite
|
Sign up to set email alerts
|

Isomery‐Dependent Miscibility Enables High‐Performance All‐Small‐Molecule Solar Cells

Abstract: Nonfullerene polymer solar cells develop quickly. However, nonfullerene small-molecule solar cells (NF-SMSCs) still show relatively inferior performance, attributing to the lack of comprehensive understanding of the structure-performance relationship. To address this issue, two isomeric small-molecule acceptors, NBDTP-F out and NBDTP-F in , with varied oxygen position in the benzodi(thienopyran) (BDTP) core are designed and synthesized. When blended with molecular donor BDT3TR-SF, devices based on the two isom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 57 publications
2
52
0
Order By: Relevance
“…The similar phenomenon on phase separation degree variation can also be observed from TEM images of the binary and the ternary blend films, as exhibited in Figure c. The dark and bright regions in TEM image are normally assigned as acceptor‐rich and donor‐rich domain, respectively . No obvious characteristics can be observed from the TEM image of PM6:T6Me blend films.…”
Section: Resultssupporting
confidence: 74%
“…The similar phenomenon on phase separation degree variation can also be observed from TEM images of the binary and the ternary blend films, as exhibited in Figure c. The dark and bright regions in TEM image are normally assigned as acceptor‐rich and donor‐rich domain, respectively . No obvious characteristics can be observed from the TEM image of PM6:T6Me blend films.…”
Section: Resultssupporting
confidence: 74%
“…However, these acceptors have non‐negligible shortcomings: the E loss is relatively large that is commonly between 0.6 and 0.8 eV and their absorption edges are at around 765–800 nm that cannot take full advantage of the light in near‐infrared (NIR) region, largely limiting the increase in J sc . NBDTP‐F out ( E g opt : 1.41 eV) reported by Zhu and co‐workers and 6TIC ( E g opt : 1.37 eV) by Jen and co‐workers that have redshifted absorption spectra achieved PCEs of 11.2% and 12.08% with high J sc s, 21.87 and 20.44 mA cm −2 in SMSCs based on BDT3TR‐SF:NBDTP‐F out and ZnP‐TBO:6TIC blends, respectively. Therefore, excellent and matched photoelectric properties are the primary conditions in obtaining high‐performance SMSCs.…”
Section: Photovoltaic Parameters Of Bsftr:y6‐based Smscs Under the Ilmentioning
confidence: 79%
“…Compared with polymer-based OSC, NFSM-OSC is more suitable as a research model device, which can more easily establish clear relationships between the structure and performance [4][5][6][7][8]. However, the power conversion efficiencies (PCEs) of current state-of-the-art NFSM-OSCs are still much lower than that of polymer-based OSCs because small molecules cannot form pre-aggregation in solution like most high-performance polymers [9-11], and have similar acceptor-donor-acceptor (A-D-A) skeleton structures with high efficiency non-fullerene acceptors, making it difficult to regulate their morphology [12][13][14][15][16][17][18][19][20][21]. To date, though considerable efforts have been made in the research of NF acceptors and a number of high-performing materials have been reported, the study on small molecule donors for efficient NFSM-OSCs is relatively lagging [1, [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%